2014
DOI: 10.1371/journal.pone.0114697
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogel: A Nano-Matrix Scaffold with Potential Application in Cardiac Regeneration Using Mesenchymal Stem Cells

Abstract: 3-Dimensional conditions for the culture of Bone Marrow-derived Stromal/Stem Cells (BMSCs) can be generated with scaffolds of biological origin. Cardiogel, a cardiac fibroblast-derived Extracellular Matrix (ECM) has been previously shown to promote cardiomyogenic differentiation of BMSCs and provide protection against oxidative stress. To determine the matrix composition and identify significant proteins in cardiogel, we investigated the differences in the composition of this nanomatrix and a BMSC-derived ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…Natural multicomponent ECMs derived from tissues have also been used in 3D to influence cell differentiation toward cardiomyocytes. Cardiogel, which is derived from cardiac fibroblasts, has been shown to control differentiation of bone marrow-derived stem cells toward a cardiomyocyte phenotype [38]. The components of cardiogel have been characterized and contain laminins, fibronectin, Col I, Col III, and a variety of proteoglycans [39].…”
Section: In Vitro Control Systems To Evaluate Cell-cecm Interplay At mentioning
confidence: 99%
“…Natural multicomponent ECMs derived from tissues have also been used in 3D to influence cell differentiation toward cardiomyocytes. Cardiogel, which is derived from cardiac fibroblasts, has been shown to control differentiation of bone marrow-derived stem cells toward a cardiomyocyte phenotype [38]. The components of cardiogel have been characterized and contain laminins, fibronectin, Col I, Col III, and a variety of proteoglycans [39].…”
Section: In Vitro Control Systems To Evaluate Cell-cecm Interplay At mentioning
confidence: 99%
“…Compared to natural scaffolds which are derived from destroyed ECM, decellularized ECM‐derived scaffolds are advantageous to preserve the complex ECM architecture and thus to maintain cell‐matrix interactions, which are uneasy to achieve by synthetic polymer scaffolds . For example, Verma and co‐workers developed several ECM‐derived scaffolds, termed as ‘cardiogel’, to repair infarcted myocardial tissues . Cardiogel promoted proliferation, adhesion and migration of BMSCs while aiding cardiomyogenic differentiation and angiogenesis .…”
Section: Type Of Polymers and Design Strategiesmentioning
confidence: 99%
“…[26,27] For example, Verma and co-workers developed several ECM-derived scaffolds, termed as 'cardiogel', to repair infarcted myocardial tissues. [28][29][30] Cardiogel promoted proliferation, adhesion and migration of BMSCs while aiding cardiomyogenic differentiation and angiogenesis. [30] ADSCs embedded in decellularized adipose tissue (DAT)-derived ECM scaffold accelerated in vivo fat regeneration through enhanced adipogenesis and angiogenesis.…”
Section: Biodegradable Scaffold To Promote Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study indicated that certain kinds whole organ ACM could support BMSCs differentiating into mature cells and expressing functional markers [26][27][28][29]. Furthermore, this type of induced cells had potential applications in regenerative therapy and tissue repair [30].…”
Section: Introductionmentioning
confidence: 99%